2017
DOI: 10.1128/jb.00124-17
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Amino Acid Residue Requirements of the RNA Polymerase (RNAP) α Subunit C-Terminal Domain for Productive Interaction between Spx and RNAP of Bacillus subtilis

Abstract: Bacillus subtilis Spx is a global transcriptional regulator that is conserved among Gram-positive bacteria, in which Spx is required for preventing oxidatively induced proteotoxicity. Upon stress induction, Spx engages RNA polymerase (RNAP) through interaction with the C-terminal domain of the rpoA-encoded RNAP ␣ subunit (␣CTD). Previous mutational analysis of rpoA revealed that substitutions of Y263 in ␣CTD severely impaired Spx-activated transcription. Attempts to substitute alanine for ␣CTD R261, R268, R289… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…As Spx binds close to the surface of α‐CTD, which contacts the upstream UP elements (Gaal et al , ; Zhang et al , ; Birch et al , ), it could act by influencing the recognition and productive interactions of α‐CTD with the specific upstream sequences. The strong transcription of rRNA promoters is also dependent on these UP‐elements (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As Spx binds close to the surface of α‐CTD, which contacts the upstream UP elements (Gaal et al , ; Zhang et al , ; Birch et al , ), it could act by influencing the recognition and productive interactions of α‐CTD with the specific upstream sequences. The strong transcription of rRNA promoters is also dependent on these UP‐elements (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it was recently observed that Spx interacts not only with α but also β or β′ subunits of RNAP (Birch et al , ). Such a more complex interaction or different binding mode of Spx and RNAP might also contribute to the inhibition of transcription at the rrnJ P1 promoter.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with previously reported UP elements in P trxA (terms as UPA here), UPL contained a high-consensus sequence of “AAGAAATAAT” and sheared adenine (A) and thymine (T) dinucleotide repeat tracts. This has been proven to be a crucial element for RNAP recognition and binding in B. subtilis [ 29 ]. However, there were significant differences between the two UP elements in terms of genomic location.…”
Section: Resultsmentioning
confidence: 99%
“…Oxidative stress also induces an intramolecular disulfide bond in the Spx CxxC redox switch, altering its conformation such that it interacts with RNA polymerase to regulate downstream genes (Fig. 2A) [25,26]. In B. subtilis, oxidized Spx activates over 100 genes involved in maintaining redox homeostasis (e.g.…”
Section: Spxa1/2: Disulfide Stressmentioning
confidence: 99%